Gender values in common-law marriages - Z. Kh. Kobleva (Вестник Майкопского государственного технологического университета, 2023)
Currently the institution of the family and marriage relations is undergoing serious changes due to transformational processes of the Russian society. These changes are reflected in the variability of forms and models of the modern family and the common-law marriage is universally popular.In the context of the modernization of society, traditional gender stereotypes are being eroded, leading to a revision of established behavioral norms and social roles in the family, forming the value-motivational foundations of marriage.The Methods. The works of domestic and foreign scientists who studied the peculiarities of the gender perspective in the system of family and marriage relations have become the theoretical basis of the research. The works of Russian sociologists and the results of an independent sociological study conducted within the framework of this problem have become the empirical basis.The Results. The thesis has been confirmed that the distribution of social roles between a man and a woman in a common-law marriage is contradictory, revealing the features of the gender display, significantly different from the traditional system of gender interaction.Practical significance. The conducted research confirms the need to create a comprehensive system of knowledge about the family, prepare the younger generation for future family and marriage relations that contribute to the preservation of the basic values of the traditional family.